Peran Dinas Kehutanan Dalam Upaya Penanggulangan Tindak Pidana Illegal Logging Di Kabupaten Langkat (Studi Kasus: Dinas Kehutanan Kabupaten Langkat) - Muhammad Rifkih Alfaris; Rafiqi Rafiqi; Rizkan Zulyadi (JUNCTO: Jurnal Ilmiah Hukum, 2021)
The problem of illegal logging is actually a very complex matter. The current forest problems faced are the responsibility of the government. So that in this study the authors raised the issue of the role and obstacles faced by the forestry service in tackling the crime of Illegal Logging. The objectives to be achieved in this study are to determine the role of the forestry service and the obstacles faced by the forestry service in tackling the Illegal loggin crime. The method used in this study is an empirical juridical approach, which in other words is a type of sociological research and can also be called field research, which examines the applicable legal provisions and what happens in the reality of society. Illegal logging countermeasures can be done through a combination of preventive (preventive) efforts, countermeasures (repressive) and monitoring efforts (detection) Obstacles felt by the Langkat District Forestry Office in tackling illegal logging crime, namely inadequate personnel, lack of understanding of the community about the importance of forests, the community's lack of understanding of forestry rules, the lack of advice and infrastructure that supports the preservation of forests